(untitled) (Nativa, 2024)
Compost-bioremediation was adopted to explore the sustainability of using a biological system of microorganisms in a mature, cured compost to break down diesel oil contaminants in soil. The process involved mixing agricultural wastes, including fruitwaste, sawdust, and sheep manure. Periodic sampling from vessels was carried out at the 15-day interval for TPH analysis and the isolation and enumeration of bacteria. Organic waste and soil contaminated with diesel oil were left outdoors for 90 days for degradation. The effectiveness of composting-bioremediation processes relies on diverse microbes. Therefore, parameters such as the C/N ratio (25–30), moisture content, and aerobic conditions are crucial. Manual rotating is necessary for optimal bioremediation. The results show that the biodegradation of diesel oil in soil was 86%–89%, higher than that of control (40%). This increase in biodegradation was due to nutrients in organic waste matter soil, which enhanced the microbes’ degradation capabilities. The results from chemical and toxicity assays showed the efficacy of composting treatment for hydrocarbon removal with a germination index of 88.17%., 80.67%, and 92.04%, respectively. This research is the transformation of diesel oil contaminants into less detrimental chemicals by microorganisms in organic waste mixed into the soil. Keywords: aerobic composting; organic waste; bioremediation; environmental recovery; degraded areas; environmental contamination. Biorremediação aprimorada de contaminantes de óleo diesel no solo RESUMO: A biorremediação foi adotada para explorar a sustentabilidade do uso de um sistema biológico de microrganismos em um composto maduro e curado para decompor os contaminantes do óleo diesel no solo. O processo envolveu a mistura de resíduos agrícolas, incluindo resíduos de frutas, serragem e esterco de ovelha. Amostras periódicas dos vasos foram realizadas com intervalo de 15 dias para análise de TPH e isolamento e enumeração de bactérias. Os resíduos orgânicos e o solo contaminado com óleo diesel ficaram ao ar livre por 90 dias para degradação. A eficácia dos processos de compostagem-biorremediação depende de diversos microrganismos. Parâmetros como a relação C/N (25–30), teor de umidade e condições aeróbicas são cruciais, sendo necessária a rotação manual para uma biorremediação ideal. Os resultados mostram que a biodegradação do óleo diesel no solo foi de 86% a 89%, superior à do controle (40%). Este aumento na biodegradação deveu-se aos nutrientes dos resíduos orgânicos do solo, que aumentaram a capacidade de degradação dos micróbios. Os resultados dos ensaios químicos e de toxicidade mostraram a eficácia do tratamento de compostagem para remoção de hidrocarbonetos com índice de germinação de 88,17%, 80,67% e 92,04%, respectivamente. Esta pesquisa consiste na transformação de contaminantes do óleo diesel em compostos químicos menos prejudiciais, por microrganismos presentes em resíduos orgânicos misturados ao solo. Palavras-chave: compostagem aeróbica; resíduos orgânicos; recuperação ambiental; áreas degradadas; contaminação ambiental.